A survey on plankton & primary productivity of Kelantan River systems - Hashim, Rohasliney (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
A two year study (January 2008 - December 2010) of plankton and primary productivity was conducted in Kelantan and Pengkalan Chepa rivers. These two rivers are considered as main river of Kelantan River Systems. Kelantan River is influenced by intensive sand mining and urbanization which at this moment could be categorized as CLASS Ill river. Meanwhile Pengkalan River is influenced by industrialization and was categorized as CLASS Ill river by Department of Environment. Zooplankton and phytoplankton are included in this study. However, the identification is yet to be completed. At this moment, there were 955 individuals of zooplankton were identified in Kelantan River, which representing 13 families and 50 species while 1260 individuals were identified in Pengkalan Chepa River which consists of 11 families and 35 species. The most dominant and abundant species in Pengkalan Chepa river was Monostyla lunaris while Lecane elasma dominated the Kelantan River. The net primary productivity value for majority of the stations in the study site showed the negative value. This indicates that the more oxygen was consumed than produced.